Depiction of Ardhanareshwar - Temples of India Project Team (Jio Institute, 2024)
A syncretic representation adorns the kakshasana (seat backs) niche in the form of Ardhanareshwar, embodying the divine union of Shiva and Uma. Shiva’s right half and Uma’s left half seamlessly blend into a single divine form, symbolizing the inseparable nature of masculine and feminine energies. While the figure originally had four arms, only the upper two remain intact. Shiva’s side wields a pointed weapon, signifying his power, while Uma’s side holds a pushpa (flower), representing her nurturing aspect. At the bottom, Nandi, Shiva’s mount, accompanies his side, while Uma’s side features a kalasha (pitcher) adorned with verdant vegetation, symbolizing fertility and abundance. It is significant because both the syncretic images of Harihara and Uma-Maheshvara connect Vishnu and Uma with vegetal growth, symbolizing prakriti (nature), while Shiva represents purusha (essence).